DAMPAK DEFORESTASI TERHADAP DINAMIKA SOSIAL DAN EKONOMI MASYARAKAT PESISIR BIMA: STUDI SOSIOLOGI LINGKUNGAN DI WILAYAH RAWAN BENCANA - Anwar, Anwar; Supriadi, Supriadi (Nusantara Hasana Journal, 2025)
The coastal area of ​​Bima Regency is one of the areas prone to natural disasters, especially flooding. This phenomenon is triggered by high rainfall intensity, ecosystem damage, and suboptimal environmental management. The impact is not only in the form of material losses, but also significant changes in the social dynamics of the community. Deforestation in Bima Regency, especially due to the conversion of forests to corn fields, has had a significant impact on the social and economic aspects of coastal communities. This study aims to analyze the impact of deforestation on the social and economic dynamics of Bima’s coastal communities and explore the role of local wisdom, specifically the philosophy of Nggahi Rawi Pahu ("words according to actions"), in efforts to adapt and mitigate these impacts. This study evaluates the impact of deforestation on the social and economic dynamics of coastal communities in Bima, Regency/City (NTB), an area that is also vulnerable to disasters (flash floods, erosion landslides). The analysis combines satellite forest cover data (Global Forest Watch / KLHK data), local literature review, and interview/questionnaire surveys of coastal communities. The results show that local forest cover loss, watershed and mangrove degradation are directly proportional to declining coastal fisheries productivity, increased flooding and erosion, and changes in livelihood strategies that increase socio-economic vulnerability. (Forest cover figures source: Global Forest Watch and regional reports/local studies).